Pengembangan Sistem Career Center untuk Departemen Konseling dan Pengembangan Karir (DKPK) Universitas Esa Unggul - Herdiana, Andika; Dewanto, Joko (Lembaga Penerbitan Universitas Esa Unggul, 2013)
The Departemen Konseling dan Pengembangan Karir (dkpk), is a departments in esa unggul university that moves in the field of service center for a career and job fair. Dkpk as of service center for a career, help the alumni to look for a job, and to improve career. Dkpk work, as an exchange serves as bridge between job seekers ( job seeker ) and employer ( employer ), where between job seekers and employer this is to be formed an information that is job vacancies. So far, the employer always have difficulty in acquiring employee candidates in accordance with the criteria vacancy. The great number of applicants with kriteria-kriterianya data candidates each cause problems for both employer in determine a candidate applicants work exact conformity to the needs of the company. Therefore, required a the support system decision that could ease firm in determine a candidate a suitor who exactly corresponding criteria vacancy expected. With the existence of the application of the determination of a candidate applicants work dna-based the web being a candidate of applicants would obtain work in accordance with the criteria vacancy. A candidate a suitor who according to be confirmed to perform phases recruitment available at the company. Selanjutnya adalah the company perform the process of recruitment as usual.Keywords: Departemen Konseling dan Pengembangan Karir, Job Seeker, EmployerÃ‚Â